Climatic characteristics and the temperature regime of asphalt pavements - Jan Corej; Martin Korenko; Eva Remisova (Communications - Scientific letters of the University of Zilina, 2004)
Traffic density and climate are important external factors influencing pavement mechanics. Climatic conditions influence the service life of materials, damage to roads etc. In many countries the climatic characteristics are implemented into calculation systems for pavement construction. The importance of the implementation of climate characteristics into the calculation systems is increasing in the context of global climatic processes and changes, especially the changes in air temperature. The aim of the following paper is to highlight the changes of climatic characteristics used in highway engineering and their effect on the change of pavement thermal flow.